Evaluation of pathomorphological changes and survival after selective intraarterial polychemotherapy of locally advanced breast cancer - Bondar, G. V.; Sedakov, I. E.; Balashova, O. I.; Khomenko, A. V. (Морфологія / Morphologia / Morfologìâ, 2011)
The pathomorphological changes (pathologic response) and survival of patients with locally advanced breast cancer (BC) were analyzed for the 89 patients treated with selective intraarterial polychemotherapy (PCT) in neoadjuvant mode and 46 treated with intravenous PCT in the same mode (control). More significant pathomorphological response after the treatment of BC in the neoadjuvant mode was achieved after selective intra-arterial PCT (p<0,01). In the intraarterial PCT group pathomorphosis grade 4 was observed in 16.9% (control – 8.70%), grade 3 – 37,0% (control – 28.3%), grade 2 – 46,1% (control – 26,1%). In the control group 1 degree pathomorphosis was in 26.1% of patients, no pathologic response – in 10,9%. In patients with pathomorphosis of 2-4 degrees in intraarterial PCT group 5-year survival increases by 0,90-5,60% compared with the control, 10-year-old survival – by 5,60-11,6%. Survival tended to increase with the degree of pathomorphosis without statistical differences in groups of intraarterial and intravenous PCT for each year of observation. The average life expectancy for the intraarterial PCT group was 4,61±0,02 years, for the control group – 4,19±0,05 (p<0,001). For 1-7 years difference in survival was within 5,8-9,5%. The best results are observed after seventh year: 7-10-year survival in intraarterial PCT group was 38.2%, in the control group – 23,9%.